2020
DOI: 10.1016/j.ihj.2020.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and long-term prognosis of ischemic and non-ischemic cardiomyopathy

Abstract: Objectives The different etiology of HF has different prognostic risk factors. Prognosis assessment of ICM and NICM has important clinical value. This study is aimed to explore the predicting factors for ICM and NICM. Methods 1082 HFrEF patients were retrospectively enrolled from Jan. 01, 2016 to Dec. 31, 2017. On Jan. 31, 2019, 873 patients were enrolled for analysis excluding incomplete, unfollowed, and unexplained data. The patients were divided into ischemic and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…21 Similar to the results of previous studies, our study showed a significant relationship between a high BNP value and mortality. 24 However, the difficulty of access to this parameter and its high cost limits its use in clinical practice. In addition, BNP values may be affected by differences in age, gender, body weight, and laboratory kits.…”
Section: Discussionmentioning
confidence: 99%
“…21 Similar to the results of previous studies, our study showed a significant relationship between a high BNP value and mortality. 24 However, the difficulty of access to this parameter and its high cost limits its use in clinical practice. In addition, BNP values may be affected by differences in age, gender, body weight, and laboratory kits.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that IHF has a worse prognosis than NIHF and the parameters such as advanced age, poor NYHA functional class and impaired renal functions are associated with the severity and prognosis of HF 34 35. In particular, lower LVEF is a major risk factor for cardiac and all-cause mortality 36.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic cardiomyopathy (ICM) results from coronary artery disease (CAD) and myocardial infarction (MI) while non-ischemic cardiomyopathy (NICM) has a variety of etiologies including genetic, viral, toxic and idiopathic. Earlier epidemiological surveys and large-scale clinical trials suggested that the prognosis of ICM patients is worse than NICM patients [2,3], yet the guideline-directed therapy for systolic dysfunction remains the same regardless of etiology. [4] Thus, a better understanding of disease mechanisms and developing etiology-specific therapeutic strategies are critical to improve patient care.…”
Section: Introductionmentioning
confidence: 99%